Control of grid side converter in wind power based PMSG with PLL method - Rania Moutchou; Ahmed Abbou (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Wind power is one of the most promising renewable energy sources. Due to a constantly increasing penetration rate in power grids in order to comply with interconnection requirements. This article targets the impact of a permanent magnet synchronous generator (PMSG) which is the subject of most attention due to low cost and maintenance requirements, driven by a wind turbine with the necessary power electronic converters that allow wind turbines to operate at variable speed, and connected to the grid for power generation more efficiently by the phase-locked loop (PLL) method in order to synchronize it. Thus, the proposed control technicals are based on vector control (VC) to achieve maximum power point tracking (MPPT), keep the DC link voltage constant, and control the speed and current at the generator side and grid side in PMSG which provides controllability of the reactive power supplied to the network. Therefore, the response of the PLL is analyzed and the simulation results of the dynamic model of the system is developed in Matlab / Simulink. The study results exhibit the excellent performance with high robustness, by improving the system efficiency to 98.72%.